A case of endophthalmitis associated with gonococcal sepsis - T. A. Krasnovid; I. V. Svystunov; O. S. Sidak-Petretskaia; N. I. Bondar (Ukrainian Society of Ophthalmologists, 2021)
Background: Gonococcal ocular lesions develop most commonly due to poor hygiene habits, when the infection is transmitted by eye-hand contact; in addition, they may develop when the infection is transported to the eye as a result of hematogenous or lymphogenous spread. Purpose: To present a rare case of endophthalmitis secondary to gonococcal sepsis, and to highlight its clinical features. Material and Methods: Visual acuity assessment, comprehensive eye examination, and microbiological examination. Results: Patient's history was significant for acute suppurative gonococcal prostatitis (with acute retention of urine, and severe sepsis with liver abscess, and suppurative tonsillitis), for which he had been treated as an in-patient at the Department of Urology of the city hospital. In addition, he had suppurative blepharitis of the left eye. A week after he was discharged from the Department of Urology, he was hospitalized to the Department of Ocular Trauma of the Filatov institute with the diagnosis of endophthalmitis in the left eye. The patient poorly responded to treatment, and clinical manifestations of endophthalmitis were becoming more and more severe. He underwent evisceration of the left eye. Conclusion: Consultations of allied health professionals and multiprofessional management of gonorrhea patients are required to prevent complications in various organs and systems, should gonococcal sepsis develop.